A Review on Exploratory based Learning Implementation by Integrating Technology Strategy in Teaching and Learning - Aryanie Bahrudin, Ida; Alias, Maizam (International Journal of Psychosocial Rehabilitation, 2020)
As an educator, no matter how much experience we have, there are always challenges to face in the classroom. Today, how people learn and practice something that they learn in everyday life is rapidly shifting. The integration of technology strategy in teaching and learning enables students to explore environments, reality, and virtual experiences. One of the learning strategies that supports this notion of learning is exploratory-based learning (EBL). This study examines the implementation of EBL in education concerning its definition and technology integration. Based on the literature reviewed, the EBL learning model extends from the Kolb model of learning, but it takes place in a cyclical mode following four steps: concrete experience, observation and reflection, forming abstract concepts, and testing in new situations. Technology integration in EBL that focuses on learning practices is identified to be applicable in order to improve learning experiences among students in Malaysia.